HUBUNGAN ANTARA KEDALAMAN SINUS FRONTALIS DAN MATURASI TULANG TANGAN: CORRELATION BETWEEN FRONTAL SINUS DEPTH AND HAND WRIST MATURITY - Harryanto Wijaya; Adi Hidayat; Irawati Gandadinata; Joko Kusnoto (TALENTA, 2009)
The appropriate planning of orthodontic therapy with regard to appliance selection, information on the patient’s stage ofsomatic maturity is needed. Hand wrist maturity has been shown to be closely related with the pubertal growth spurt;therefore hand wrist radiographs have been recommended for indirect assesment of somatic maturity. However, theroutine use of hand wrist radiographs has lately been questioned from the radiation-hygiene, safety point of view. In arecent cephalometric investigation, it was found that the frontal sinus development showed a growth rhythm similar to thebody height development. Furthermore, it has been proposed that frontal sinus enlargement follows general bone growthbut little evidence has been shown. The objective of this study was to investigate the correlation between frontal sinusdepth and hand wrist maturity in Deuteromalayid group aged 7 to 17 years. A cross sectional study was conducted in 138subjects (69 males, 69 females). The frontal sinus depth and hand wrist maturation was determined using Ertürk’s andFishman’s method, respectively. The result of this study showed that there was a moderate correlation between frontalsinus depth and hand wrist maturity in males (r = 0.608) and females (r = 0.647). From this study, it can be concludedthat the usage of frontal sinus depth to substitute hand wrist maturity to assess the skeletal maturity is not appropriateenough.